Digital repertoires of poetry metrics: towards a Linked Open Data ecosystem - Rio Riande, María Gimena del (2016)
This paper presents work-in-progress of the POSTDATA project. This project aims to provide means to solve the interoperability issues that exist among the digital poetry repertoires. These repertoires hold data of poetry metrics that is locked in their own databases and it is not freely available to be compared and to be used by intelligent machines that could infer over the data. The POSTDATA project will use Linked Open Data (LOD) technologies to overcome the interoperability problems. POSTDATA is developing a metadata application proFIle (MAP) for the digital poetry repertoires, a construct that enhances interoperability.This development follows the method for the development of MAP (Me4MAP).A MAP for the digital poetry repertoires will open doors for this repertoires to be able to structure the data with a common model in order to publish it as Linked Open Data. This paper presents how this MAP is being developed so far.